Selection of Ground Motion Prediction Equations for Seismic Hazard Analysis of Peninsular India. Issue 5 (3rd July 2016) - Anbazhagan, P.; Sreenivas, M.; Ketan, B.; Moustafa, S. S. R.; Al-Arifi, N. S. N.
Abstract : Seismic hazard analysis provides an estimation of seismic hazard parameters like peak ground acceleration (PGA) or spectral acceleration (SA) for different periods. The extent of ground shaking and the hazard values at a particular region are estimated using ground-motion prediction equations (GMPEs)/attenuation equations. There are several GMPEs applicable for the region to estimate the PGA and SA values. These equations may result in higher or lower PGA and SA values than the region specific reported values, which are based on the parameters involved in the development of GMPEs. In this study, an attempt has been made to identify the best GMPEs for various parts of Peninsular India (PI) by performing an "efficacy test, " which make use of the average log likelihood value (LLH). Various intraplate earthquakes such as Coimbatore earthquake, Satpura earthquake, Anjar earthquake, Koyna earthquake, Bhadrachalam earthquake, Broach earthquake, Shimoga earthquake, Killari earthquake, Jabalpur earthquake, Pala earthquake, Kottayam earthquake, and Bhuj earthquake have been considered for the same. Macroseismic intensity maps of these earthquakes have been digitalized and European Macroseismic Scale (EMS) values at the surface have been synthesized. PGA value determined from each GMPE for known magnitude and hypocentral distances are then converted to EMS values. These calculated EMS values have been used to estimate LLH values which are further used to compute Data Support Index (DSI), rank and weights corresponding to a particular GMPE. Conventionally, LLH values are estimated for the entire distance range and GMPEs are ranked accordingly, but in this study, the LLH is calculated for the distance segments of 0-200 km and 200 km to maximum damaged distance in the region based on Isoseismal maps. If the maximum damaged distance is less than 200 km, a distance segment up to 200 km is adopted. Comparison between the rankings of the GMPEs in segments 0–200 km and 200–maximum damage distance is presented here. Segment-based GMPEs ranking shows different ranks, DSI and weights for each GMPE as compared to ranking considering entire distance. Finally, this study provides a list of GMPEs that perform best for the estimation of ground motion parameters in different parts of PI. This study shows that the GMPEs of HAHO-97, ATK-08, CAM-06, TOR-02, NDMA-10, and PEZA-11 perform better for the estimation of ground motion in most part of PI in the distance segment 0–200 km. The GMPEs of TOR-02, RAIY-07, and RAIY-07 (PI) perform best in the 200-maximum damage distance segment.